2008
DOI: 10.21608/eajbsa.2008.15753
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of entomopathogenic fungus Verticillium lecanii (Zimmermann) Vieges and the predator Chrysoperla carnea (Stephens) against cowpea aphid, Aphis craccivora (Koch) on faba bean in EGYPT

Abstract: Evaluation of entomopathogenic fungus Verticillium lecanii (Zimmermann) Vieges and the predator Chrysoperla carnea (Stephens) against cowpea aphid,Aphis craccivora (Koch) on faba bean in EGYPT ABSTRACT Three tested treatments of the entomopathogenic fungus Verticillium lecanii (Zimmermann) Vieges, the predator Chrysoperla carnea (Stephens) and V. lecanii followed by release of C. carnea in faba bean field for controlling cowpea aphid, Aphis craccivora (Koch) compared with control were conducted. The first trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…For females (24 hours), treated with concentrations of (10 5 , 10 3 and 10 1 ) spore / mL of survival for (11.6, 12.0 and 12.1) days respectively Compared to control treatment, the female of survival was 18.1 days. The results of a study by Abd El-Gawad and Atef (2008) showed the success and effectiveness of using the Verticillium lecanii fungus suspension at 10 8 spore / mL and the C. carnea ( Stephens) larvae second instar together in the control of aphis bean Aphis craccivora in Egypt. This study was revealed that the spore suspension of the Verticillium lecanii was very effective against E.cautella and it can be used as a biocontrol agent against this pest.…”
Section: Effect Of Suspension Fungal Of Vlecanii In the Mortality Ofmentioning
confidence: 99%
“…For females (24 hours), treated with concentrations of (10 5 , 10 3 and 10 1 ) spore / mL of survival for (11.6, 12.0 and 12.1) days respectively Compared to control treatment, the female of survival was 18.1 days. The results of a study by Abd El-Gawad and Atef (2008) showed the success and effectiveness of using the Verticillium lecanii fungus suspension at 10 8 spore / mL and the C. carnea ( Stephens) larvae second instar together in the control of aphis bean Aphis craccivora in Egypt. This study was revealed that the spore suspension of the Verticillium lecanii was very effective against E.cautella and it can be used as a biocontrol agent against this pest.…”
Section: Effect Of Suspension Fungal Of Vlecanii In the Mortality Ofmentioning
confidence: 99%